Problematika dakwah dan pendidikan pada masyarakat pedalaman Tau Taa Wana Morowali Utara - Agusman,; Majid, Zamakhsyari Abdul; Hamid, Abdul; Hanif, Muhammad (Tawazun: Jurnal Pendidikan Islam, 2023)
The Tau Taa Wana inland community in North Morowali is an ethnic minority group living in remote and isolated areas of Indonesia. They have strong traditional cultures and beliefs, but also face challenges in accessing education and accepting wider religious proselytizing. Limited accessibility, lack of resources, and lack of educational and communication infrastructure are factors that influence the process of da'wah and education in this region. The purpose of this study is to understand the challenges faced in delivering religious da'wah and providing education to the rural communities of Tau Taa Wana. The scope of research includes an analysis of social, economic, cultural, and infrastructural factors affecting da'wah and education in the region. This study used a qualitative approach by conducting in-depth interviews and participatory observations with rural preachers. The data obtained were analyzed descriptively and interpretively to gain a comprehensive understanding of da'wah and education issues. The results of this study show that da'wah and education in the rural communities of Tau Taa Wana face various challenges. Limited infrastructure, long distances, and lack of access to educational resources are the main obstacles in providing formal education. Da'wah and education in the rural communities of North Tau Taa Wana Morowali face serious challenges that affect their efforts to improve religious knowledge and access to formal education. To overcome this problem, comprehensive efforts are needed, including improving educational infrastructure, training qualified religious teachers, and developing curricula that take into account the cultural context of rural communities. In addition, collaboration with government, educational institutions, and community organizations needs to be improved. Abstrak Masyarakat pedalaman Tau Taa Wana di Morowali Utara adalah kelompok etnis minoritas yang hidup di daerah terpencil dan terisolasi di Indonesia. Mereka memiliki budaya dan kepercayaan tradisional yang kuat, namun juga menghadapi tantangan dalam mengakses pendidikan dan menerima dakwah agama yang lebih luas. Keterbatasan aksesibilitas, kurangnya sumber daya, dan minimnya infrastruktur pendidikan dan komunikasi menjadi faktor-faktor yang mempengaruhi proses dakwah dan pendidikan di wilayah ini. Tujuan penelitian ini adalah untuk memahami tantangan yang dihadapi dalam menyampaikan dakwah agama dan memberikan pendidikan kepada masyarakat pedalaman Tau Taa Wana. Ruang lingkup penelitian meliputi analisis terhadap faktor-faktor sosial, ekonomi, budaya, dan infrastruktur yang mempengaruhi dakwah dan pendidikan di wilayah ini. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan wawancara mendalam dan observasi partisipatif dengan para da’i pedalaman. Data yang diperoleh dianalisis secara deskriptif dan interpretatif untuk mendapatkan pemahaman yang komprehensif tentang permasalahan dakwah dan pendidikan. Hasil penelitian ini menunjukkan bahwa dakwah dan pendidikan di masyarakat pedalaman Tau Taa Wana menghadapi berbagai tantangan. Keterbatasan infrastruktur, jarak yang jauh, dan minimnya akses terhadap sumber daya pendidikan menjadi hambatan utama dalam memberikan pendidikan formal. Dakwah dan pendidikan di masyarakat pedalaman Tau Taa Wana Morowali Utara menghadapi tantangan serius yang mempengaruhi upaya mereka untuk meningkatkan pengetahuan agama dan akses pendidikan formal. Untuk mengatasi masalah ini, diperlukan upaya yang komprehensif, termasuk peningkatan infrastruktur pendidikan, pelatihan tenaga pengajar agama yang berkualifikasi, dan pengembangan kurikulum yang memperhatikan konteks budaya masyarakat pedalaman. Selain itu, kolaborasi dengan pemerintah, lembaga pendidikan, dan organisasi masyarakat perlu ditingkatkan.